Tour Company’s Service Quality and Tourists’ Revisit Intention in Arusha Region Tourist Destinations - Majaliwa, Dioscory; Magasi, Chacha (Journal of Consumer Sciences, 2024)
This study investigated the effect of tour companies’ service quality on tourists’ intention to revisit tourism destinations in the Arusha region. The general objective of this study is to examine the effect of tour companies’ service quality on tourists’ revisit intentions in Arusha tourist destinations. This study used a cross-sectional research design and employed a survey as the data-collection method. Respondents were selected using simple random sampling; 384 respondents were included in this study. Questionnaires were used to collect data from respondents at Arusha tourist destinations. Data were analyzed using descriptive statistics and a binary logistic regression model. The findings revealed that tangibles, responsiveness, and assurance had positive indices, implying that tourists were delighted by the service provided. The study establishes a positive relationship between tangibles, responsiveness, and assurance dimensions and tourists' revisit intentions, with a specific emphasis on the statistically significant connections of tangibles and responsiveness at p < 0.05, emphasizing the need to enhance these aspects to promote repeat visits to Arusha tourist destinations. However, assurance was found to have an insignificant relationship with tourists’ intentions to revisit. Therefore, tour companies, government entities, and tourism authorities should focus on improving tangibles and responsiveness dimensions to enhance tourists' intention to revisit.